Analysis of patients unable to return to play following arthroscopic Bankart repair. Issue 4 (August 2022) - Hurley, Eoghan T.; Davey, Martin S.; Mojica, Edward S.; Montgomery, Connor; Gaafar, Mohamed; Jazrawi, Laith M.; Mullett, Hannan; Pauzenberger, Leo
Abstract: Purpose: The purpose of this study was to analyze patients that did not return to play (RTP) following arthroscopic Bankart repair (ABR) compared to those who did RTP, and analyze factors associated with not returning to play. Methods: A retrospective review of patients who underwent ABR, and subsequently did not RTP after a minimum of 24-month follow-up was performed. Additionally, these were pair matched in a 3:1 ratio for age, gender, sport and level of pre-operative play with a control group who RTP. Patients were evaluated for their psychological readiness to return to sport using the SIRSI score. Multivariate regression models were used to evaluate factors affecting RTP. Results: The study included a total of 52 patients who were unable to RTP and 156 who returned to play. Ten patients (19.2 %) who did not RTP passed the SIRSI benchmark of 56 with a mean overall score of 39.8 ± 24.6, in those who returned 73.0 % passed the SIRSI benchmark of 56 with a mean overall score of 68.9 ± 22.0 (p < 0.0001 for both). The most common primary reasons for not returning were 27 felt physically unable to return, whilst 21 felt it was a natural end to their career or their lifestyle had changed. Multi-logistic regression revealed that 4 of the 12 components of the SIRSI score (p < 0.05 for all) and SSV (p = 0.0049), were the factors that were associated with RTP. Conclusion: Following ABR, those that do not return to play exhibit poor psychological readiness to return to play, with multi-linear regression revealing the SIRSI questions associated with fear of re-injury were associated with a lower rate of RTP. Additionally, functional limitations were found to be associated with a lower rate of RTP. Level of evidence: Level III; Retrospective Comparative Cohort Study. Highlights: Those that do not RTP exhibit poorer psychological readiness to RTP. Fear of re-injury questions were associated with a lower rate of RTP. Pain and functional limitations were associated with a lower rate of RTP.